Novel Therapeutic Approaches to the Treatment of Chronic Abdominal Visceral Pain - Franca Patrizi; Steven D. Freedman; Alvaro Pascual-Leone; Felipe Fregni (The Scientific World Journal)
Chronic abdominal visceral pain (CAVP) has a significant clinical impact and represents one of the most frequent and debilitating disorders in the general population. It also leads to a significant economic burden due to workdays lost, reduced productivity, and long-term use of medications with their associated side effects. Despite the availability of several therapeutic options, the management of patients with CAVP is often inadequate, resulting in frustration for both patients and physicians. This may in part be explained by the lack of understanding of the mechanisms underlying chronic pain; in contrast with acute pain in which the pathophysiology is relatively well known and has several satisfactory therapeutic options. Recently, the development of tools for brain investigation, such as functional magnetic resonance imaging, has provided new insights on the pathophysiology of chronic pain. These new data have shown that plastic changes in the central and peripheral nervous system might play an important role in the maintenance of chronic pain. Therefore, approaches aimed at the modulation of the nervous system, rather than the ones interfering with the inflammatory pathways, may be more effective for chronic pain treatment. We propose that noninvasive central nervous system stimulation, with transcranial magnetic stimulation (TMS), might be a novel therapeutic option for CAVP. This paper will present an overview of the pathophysiology and the available therapies for CAVP, focusing on the recent advances in the treatment of this pathology.